EV Markets: A Comparative Analysis between India & Nigeria - Pandey, Dr. Rudresh; Vishnoi, Dr. Sushant Kumar; Tiwari, Swarn; Onukele, Amarachi; Gupta, Himanshu Kumar (Journal of International Conference Proceedings, 2023)
This study conducts a thorough comparative analysis of the Electric Vehicle (EV) markets in India and Nigeria, two emerging economies with distinct socio-economic and infrastructural profiles. The primary objective is to comprehensively understand the factors influencing EV adoption for the consumers in these nations. We meticulously examine consumer preferences, purchasing barriers, and government role, highlighting the unique challenges in each context. We delve into the economic and policy-driven influences on the EV landscape, emphasizing Economic Factors and Economic reforms for EV in both nations. We evaluate policy frameworks in the context of national development goals and environmental objectives, encompassing Government plans and financial perks. This study also emphasizing domestic economic growth potentials. The study employs a structured questionnaire distributed to 100 respondents, resulting in 60 valid responses. This questionnaire includes 19 items for the study which are taken under to analyze or examine on the basis ofÂ  Â Electric Vehicle (EV) Market of India and Nigeria.